Ovarian Hyperstimulation and Oocyte Harvesting Prior to Systemic Chemotherapy—A Possible Pitfall in 18F-FDG PET/CT Staging of Oncologic Patients. (August 2016) - Bacanovic, Sara; Stiller, Ruth; Pircher, Magdalena; Burger, Irene A.; Huellner, Martin W.
Abstract : Abstract: A 33-year-old woman with Hodgkin disease Ann Arbor stage IIA underwent baseline 18 F-FDG PET/CT scanning. The scan showed gross multicystic enlargement of both ovaries and a nodule at the edge of the right ovary with intense FDG uptake (SUVmax = 14.8). Differential diagnosis would include ovarian lymphoma manifestation, endometrioma, and ovarian or pelvic neoplasia. However, chart analysis revealed previous superstimulation with gonadotropins and gonadotropin release hormone antagonist, and transvaginal oocyte retrieval the day before FDG PET/CT. This led to the diagnosis of ovarian hyperstimulation syndrome, with the FDG-avid focus representing a hemorrhagic follicle after transvaginal oocyte retrieval procedure.